2012
DOI: 10.1039/c2ob07172j
|View full text |Cite
|
Sign up to set email alerts
|

Expedient synthesis of pseudo-Pro-containing peptides: towards constrained peptidomimetics and foldamers

Abstract: The reaction of sulfonyl peptides containing L- or D-configured Ser or Thr with bis(succinimidyl) carbonate in the presence of a catalytic amount of a base affords, in solution or in the solid phase, the corresponding peptides with one or two, consecutive or alternate oxazolidin-2-ones (Oxd). The Oxd ring can be regarded to as a pseudo-Pro with an exclusively trans conformation of the preceding peptide bond; homochiral Oxd-containing peptides adopt extended conformations, while the presence of a D-configured O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 91 publications
0
12
1
Order By: Relevance
“…Next, to determine the role of the N-terminal protecting group (Pg) in the formation of the cyclic urethane moiety, a model peptide Pg-ASF-Rink AM with other N-terminal protecting groups such as acetyl, tosyl, and Boc was investigated (entries 7–9, Table 2 ). Contrary to earlier studies, 24 the results indicated that the formation of the cyclic urethane moiety from serine by activating the backbone peptide chain is independent of the nature of the N-terminal protecting group.…”
Section: Resultscontrasting
confidence: 99%
“…Next, to determine the role of the N-terminal protecting group (Pg) in the formation of the cyclic urethane moiety, a model peptide Pg-ASF-Rink AM with other N-terminal protecting groups such as acetyl, tosyl, and Boc was investigated (entries 7–9, Table 2 ). Contrary to earlier studies, 24 the results indicated that the formation of the cyclic urethane moiety from serine by activating the backbone peptide chain is independent of the nature of the N-terminal protecting group.…”
Section: Resultscontrasting
confidence: 99%
“…Recently, we proposed the expedient cyclization of β‐hydroxy‐α‐amino acids already embedded in a oligopeptide sequence, by treatment with disuccinimidyldicarbonate (DSC) and a base, to give oxazolidinone‐peptides (Oxd) . Depending from the stereochemistry, linear peptides including two consecutive β‐hydroxy‐α‐amino acids gave rise to sequences Oxd‐Oxd or ΔAbu‐Oxd; these scaffolds adopted well‐defined extended or folded conformations, in particular normal or inverse β‐turns of type I or II (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…Earlier attempts of utilizing DSC for the formation of the cyclic urethane moiety on Fmoc/Boc peptides were unsuccessful and led to the formation of dehydroalanine. 23 Hydrolysis of the peptide bond at the cyclic urethane moiety (B) produces an N-terminal peptide fragment (C) and the cyclic urethane modified C-terminal fragment (D).…”
Section: Site-selective Chemical Cleavage Of Peptide Bonds †mentioning
confidence: 99%